An urban walk as a teaching strategy and investigative instrument in art education. Issue 3 (1st December 2019) - Genet-Verney, Rafaèle; Marín-Viadel, Ricardo; Fernández-Morillas, Antonio
AbstractThis article explores interactions among three topics: the city, visual arts and education, all interconnected through an urban and artistic practice of walking. This reflection is carried out in three fields of thought: education, investigation and artistic creation. On an educative level, one questions how a path through the city can be a strategy for art education learning. In the research field, thanks to analysis of artistic and urbanism methodologies applied to the city, research is carried out using walking maps as tools of art and urban planning investigation. On an artistic level, aesthetic results are desired from the investigation as a result of teaching practice designed to be a creative reflection on the city. We analysed current tendencies in art education through the use of the walking path around the city and investigation using maps. We present the three educative experiences validating the use of urban walks as pedagogic strategies and instruments of investigation.